Development of Higher-Order Thinking Skills (HOTS)-Based Student Worksheets to Enhance Fifth-Grade Students’ Critical Thinking Skills in Science and Social Studies (IPAS). - Amir Pada (Global Journal Basic Education, 2026)
This study employed a Research and Development (R&D) approach using the 4D model, which consists of four stages: Define, Design, Develop, and Disseminate. The define stage involved analyzing learning needs, student characteristics, tasks, and concepts. The design stage focused on developing assessment instruments, selecting appropriate formats, and designing Higher-Order Thinking Skills (HOTS)-based learning activities. The develop stage included expert validation, product revision, and limited trials conducted with fifth-grade students. Finally, the disseminate stage involved the limited distribution and implementation of the developed worksheets. The findings revealed that the HOTS-based Student Worksheets (LKPD) were valid, practical, and effective in improving students' critical thinking skills. The developed worksheets encouraged active student participation, promoted analytical thinking, and connected learning content to real-life contexts. This study contributes to the development of innovative instructional materials that align with the demands of 21st-century learning and provides practical implications for enhancing the quality of elementary education.